Logic for Programming, Artificial Intelligence, and Reasoning 20th International Conference, LPAR-20 2015, Suva, Fiji, November 24-28, 2015, Proceedings - Davis, Martin; Fehnker, Ansgar; McIver, Annabelle; Voronkov, Andrei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the proceedings of the 20th International Conference on Logic for Programming, Artificial Intelligence, and Reasoning, LPAR-20, held in November 2015, in Suva, Fiji. The 43 regular papers presented together with 1 invited talk included in this volume were carefully reviewed and selected from 92 submissions. The series of International Conferences on Logic for Programming, Artificial Intelligence and Reasoning, LPAR, is a forum where, year after year, some of the most renowned researchers in the areas of logic, automated reasoning, computational logic, programming languages and their applications come to present cutting-edge results, to discuss advances in these fields, and to exchange ideas in a scientifically emerging part of the world.
Keywords: Computer science; Computer programming; Software engineering; Programming languages (Electronic computers).; Computer logic; Mathematical logic; Artificial intelligence; Computer Science; Software Engineering; Artificial Intelligence (incl. Robotics).; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Programming Techniques; Programming Languages, Compilers, Interpreters; Electronic books